(untitled) (Latakia University Journal -Biological Sciences Series, 2013)
جمعت عينات القشريات لينات الدرقة من عدة أوساط مائية عذبة في حوض العاصي (نهر العاصي ، بحيرة قطينة، السدود التجميعية لمياه الأمطار كالزعفران والسنديانة ، نبع التين ) في الفترة الواقعة ما بين آب 2010 وآب 2011 م . حفظت العينات في الكحول 70%. وبعد الفحص الدقيق لأفراد القشريات تم تصنيف أربعة أنواع : نوعان يتبعان لسرطانات المياه العذبة. وقد تم التمييز بينهما تبعاً للأرجل التناسلية للذكر وهما : Potamon potamios وPotamon setiger من فصيلة Potamidae وتحت نوع واحد من الجمبريات Atyaephyrra dessmarestii orintalis من فصيلة Atyidae ومن رتبة طرفيات الأرجل النوع Gammarus lacustris من فصيلة Gammaridae. تم وصف مورفولوجي دقيق لكل نوع ، مع توضيح أهم الصفات التصنيفية المميزة مرفقة بالرسوم التوضيحية والصور. The samples of Crustaceans (Malacostraca) were collected in the fresh water, from different regions of Al-Assi valley (the river, Katenah lake, the reservoirs such as Al-Zaafaranh, Al-Sindianh and from Al-teen spring), between August 2010 and August 2011. The samples were preserved in alcohol (70 %). After accurate inspection of the collected samples, there were 4 species classified, two species of freshwater belonging to true crabs were recognized by depending on the masculine organs as following: Potamon potamois and Potamon setiger from the Potamidae family, one species of shrimps Atyaephyrra dessmarestii-orintalis from Atyidae family, and only one species of amphipods which was Grammars lacustris of Gammaridae family. All examined species were described morphologically, explaining the most important classified features that distinguish these species presented with clarifying paintings and with the pictures for these features.